2018
DOI: 10.1029/2018gl080691
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Precursors for Statistical Prediction of Stratospheric Sudden Warming Events

Abstract: This work explores dynamical arguments for statistical prediction of stratospheric sudden warming events (SSWs). Based on climate model output, it focuses on two predictors, upward wave activity in the lower stratosphere and meridional potential vorticity gradient in the upper stratosphere, and detects large values of these predictors. Then it quantifies how many SSWs are preceded by predictor events and, inversely, how many events are followed by SSWs. This allows to compute conditional probabilities of futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 47 publications
3
41
0
Order By: Relevance
“…Palmer (1981) suggested that the stratospheric vortex may need to be “preconditioned” to accept a pulse of wave activity, based on observations of the 1979 event, a topic further explored by McIntyre (1982). Various studies have suggested that the strength and size of the vortex play a critical role in allowing wave activity to penetrate deep into the stratosphere (Albers & Birner, 2014; Jucker & Reichler, 2018; Kuttippurath & Nikulin, 2012; Limpasuvan et al, 2004; Nishii et al, 2009).…”
Section: Development Of Dynamical Theoriesmentioning
confidence: 99%
“…Palmer (1981) suggested that the stratospheric vortex may need to be “preconditioned” to accept a pulse of wave activity, based on observations of the 1979 event, a topic further explored by McIntyre (1982). Various studies have suggested that the strength and size of the vortex play a critical role in allowing wave activity to penetrate deep into the stratosphere (Albers & Birner, 2014; Jucker & Reichler, 2018; Kuttippurath & Nikulin, 2012; Limpasuvan et al, 2004; Nishii et al, 2009).…”
Section: Development Of Dynamical Theoriesmentioning
confidence: 99%
“…This distinction is likely a consequence of the tropopause wave source being present in the lower stratosphere already; thus, additional preconditioning in that case is less important within the stratosphere (unlike the surface wave source). This further suggests that strong polar vortex (strong negative PV gradients) combined with wave forcing could be used together for predicting the SSDs/SSWs (see also Jucker and Reichler, 2018).…”
Section: Polar Vortex Preconditioningmentioning
confidence: 85%
“…The underlying model of the ERA-20C also has a very good vertical resolution (91 vertical levels) in both the troposphere and in the stratosphere. Note that we have performed the analysis below also on JRA-55 reanalysis dataset (Kobayashi et al, 2015;, which yielded qualitatively similar results to ERA-20C, but the statistics were poor (due to small sample sizes), and are thus omitted (for brevity). Note also that while ERA-20C (constrained by surface observations only) yields qualitatively similar results to JRA-55, the results are less wellconstrained than for full-blown reanalyses (such as JRA-55).…”
Section: Model and Datamentioning
confidence: 93%
See 1 more Smart Citation
“…The mechanisms for skillful S2S prediction associated with variability from the polar vortex in the form of sudden stratospheric warming events, strong vortex events, and final warming (FW) events are explored by several contributions to the special collection (Jucker & Reichler, ; Karpechko et al, ; Lee et al, ; Butler et al, ; Domeisen et al , b). Several studies focus on the ability to resolve the key mechanisms involved in predicting stratospheric vortex variability require consideration of upward wave activity flux (e.g., Jucker & Reichler, ; Karpechko et al, ), the meridional potential vorticity gradient (Jucker & Reichler, ), accurate prediction of the Ural High (Karpechko et al, ; Lee et al, ), North Atlantic cyclones, and associated Rossby wave breaking (Lee et al, ). Studies also emphasize that the background climate patterns can extend the predictability horizon and the likelihood of these mechanisms to create a favorable environment for stratospheric variability (Rao et al, ).…”
Section: Advances In Understanding S2s Predictability and Skillmentioning
confidence: 99%